Some Features of Evaluation and Development of Vilnius University Journalism Study Programmes (2018–2021) - Vaišnys, Andrius (Žurnalistikos tyrimai, 2021)
The author discusses the changes in the Journalism study program that were made in response to the order of the Lithuanian Minister of Education and Science (2018). With this order, the minister suspended 200 study programs in 2018, including the journalism bachelor‘s study program. At Vilnius University, in response to the minister‘s decision, the program began to be changed, but the Lithuanian Constitutional Court recognized the minister‘s order as unconstitutional a little later. The evaluation of journalism studies is here: https://skvc.lt/uploads/ valuations/docs/1569806_VU%20Journalism_2021.pdf